CFD study for optimized cooling performance Influence on cooling performance of a diesel generator from using a stator - Lago, Caspian; Haidari, Mohamed Hadi (My University, 2022)
Almost every part of society relies on electricity, ranging from hospitals, supermar kets and construction sites. This dependency means that electric generators are nec essary to provide electrical power during power outages and at off-grid sites. Diesel generators are by far the most common type of generator and providing high effi ciency power generation engines are important for keeping emissions and operating costs at a minimum. The thesis will investigate if adding a stator to the cooling sys tem of the Volvo Penta D16 GENSET engine can help improve cooling performance. The D16 GENSET engines are stationary units that lack the ram effect of air to aid with cooling. This puts a high demand on the engine’s cooling system that uses a significant part of the available output power. A single axial fan produces the airflow required for cooling purposes resulting in an uneven distribution of the airflow over the radiator. The project focuses on how the distribution of airflow over the radiator can be improved by adding a stator between the fan and the radiator. Five stators with different meridional designs are evaluated, all stators are designed using the turbomachinery design program TURBOdesign suite. The CFD program STAR-CCM+ is used to simulate the flow over the radiator for the different stator cases. To determine if the stators can improve the amount of heat transferred away from the engine the airflow across the radiator and the temperature of the engine coolant is evaluated.
Keywords: Axial fan, heat exchanger, stator design, rotor-stator interaction, cooling performance, STAR-CCM+.